Rights-Based Approaches in Climate Change, Conservation and Development Initiatives: Preliminary analysis and recommendations from a review of the scholarly literature - Prouchet, L.; Sarmiento Barletti, J.P.; Larson, A.M. (CIFOR-ICRAF, 2023)
Rights-Based Approaches (RBAs) purposefully position the recognition of, respect for, and access to individual and collective rights as central to an initiative’s planning, design, implementation, monitoring process, and outcomes. In mainstream climate change, conservation, and development programs and policies, this means refocusing the relationship between ‘beneficiaries’ and ‘implementers’ to one of right holders and duty-bearers. RBAs hold growing discursive importance in relation to the rights of Indigenous Peoples and local communities (IPs and LCs) in conservation and climate change spheres and the agendas of international agencies.